Green Finance Instruments and Sustainable Industrial Transformation in the Age of Industry 5.0 - Bhandari, Om Prakash; Paudel, Sandip; Paudel, Sampurna (Academia Journal of Humanities & Social Sciences, 2026)
Recently, digital transformation has become a recognized critical facilitator of the environmental, social, and governance (ESG) performance. However, this transformation remains fragmented across the sustainability, finance, management, and technology literature. This study offers a bibliometric analysis of 478 publications (2016–2026) drawn from 155 sources, employing a PRISMA-based selection process, followed by a performance analysis and science mapping. The rapidly annual growth, with the research output of 52.04%, is concentrated geographically, particularly in China. The co-citation and keyword co-occurrence analyses reveal the converging thematic streams, encompassing the digital transformation, ESG performance, sustainability reporting, green finance, green innovation, and industry 5.0 transitions. The conceptual mapping indicates a shift from a broad digitalization discourse toward the specialized topics, such as the digital ESG, AI-enabled sustainability systems, and resilience-focused transition frameworks. The study identifies the structural imbalances in the geographic representation and conceptual fragmentation, offering a foundation for future theory-building, comparative empirical studies, and policy-oriented inquiry into the digital pathways for a sustainable transition.